Preparation of Frozen Sweet Potato (Ipomoea Batatas) Dough Base for Traditional Malaysian Fried Cakes - Mohd. Rafdi, Husni Hayati (2008)
Sweet potato dough base is popular for making traditional fried cakes in Malaysia but there has been no specific quality standard as reference for the dough preparation. The independent variables to produce the dough, i.e. mashing time (11.36 – 138.64s) and wheat flour concentration (3.79 – 46.21%) were designed using the central composite design based on Response Surface Methodology (RSM). The dough and fried cakes produced were examined for quality on the basis of physical parameters and sensory attributes. Optimal conditions for making sweet potato dough for fried cakes production were determined, by Response Surface Methodology (RSM), to be 45s of mashing time at 150rpm and 25% of wheat flour concentration. The dough base was then produced using the optimum condition and stored for 6 months at -20±2oC for quality changes observation at 1 month interval. Sweet potato paste was also included in the storage study for comparison. Unfrozen samples (dough and paste) were used as control in this study. Moisture content of frozen samples decreased with increasing of storage time and caused dehydration in samples. The water holding capacity of the samples reduced reflected by drip loss produced in paste, also by increased in paste and dough adhesiveness after frozen storage. These suggested that structure damage occurred due to frozen and frozen storage. Thus, caused the firmness and elasticity (G’) of dough and paste to increase. As the consequence, the Texture Profile Analysis (TPA) of fried cakes (firmness, cohesiveness, springiness and chewiness) were decreased. Micrographs obtained showed that all the structure of dough, paste and fried cakes collapsed, ruptured and were drier after 6 months of storage. Based on the Quantitative Descriptive Analysis (QDA), frozen dough and paste became harder to handle due to increase of adhesiveness. However, those negative changes in instrumental analysis did not influence the overall acceptability on the fried cakes. Fried cakes were still acceptable with overall acceptability score was 5.52, denotes as slightly acceptable. Freeze-thaw cycle study was conducted on sweet potato dough to investigate the stability of the dough against temperature fluctuation. Sweet potato dough and paste were exposed to 5 freeze-thaw cycles treatment for 5 weeks and the quality changes on the physical and sensory characteristics of samples were observed. Samples that stored for 5 weeks without undergoing freeze-thaw cycles were used as control. The freezethaw cycles resulted in severe damages to sweet potato dough and paste structure as the changes in moisture, drip loss, firmness, adhesiveness, storage modulus (G’) and complex viscosity (μ*) were significant (P<0.05). Due to dough changes, fried cakes became firmer with increasing in number of freeze-thaw cycles. The dough, paste and fried cakes structure became drier and many holes were developed after been exposed to 5 freeze-thaw cycles as shown in micrographs. Adhesiveness and handling ability from QDA assessment was the most affected physical characteristics. Even though freeze-thaw cycles caused severe damaged to dough structure, the fried cakes made from the dough were slightly acceptable. Keywords: Sweet potato dough, traditional fried cakes, frozen storage, freeze-thaw cycle, physical changes, sensory evaluation